Reflection on educational coaching as a practical process in the classroom (Research, Society and Development, 2020)
In recent decades, educational coaching has been proposed as a tool to help the teacher in his work and, in this way, students achieve the expected success in their learning process. To do this, there are numerous theorists who have advanced in the research of this construct and it is believed necessary to make a humble systematization of what it means to implement this process in the classroom. To carry out the proposed objective: to explore and describe research related to the application of educational coaching in the classroom; a literature review has been developed that, after conducting a content analysis, has extracted different considerations and the process to be carried out to establish a teaching-learning process in which educational coaching is measured.